Pet Animal Idiomatic Expressions in English and Kurdish: A Pragmatic Analysis - Ibrahim, Elaf M.; Muhammad, Himdad A. (KOYA UNIVERSITY JOURNAL OF HUMANITIES AND SOCIAL SCIENCES, 2022)
Animal idioms are widespread in daily life; they have become inextricably linked to human existence and language. Additionally, they have acquired additional attributive and connotative meanings – which differ from one culture to another - in addition to their literal and lexical meanings. Animal idioms are not well-investigated, especially from a pragmatic point of view. These set expressions vary from one language to another as well. Hence, this paper examines pet animal idiomatic expressions from a pragmatic perspective. The paper adopts a qualitative method for the analysis of the samples. It focuses on the similarities and differences in both English and Kurdish languages in terms of three pragmatic concepts; cooperative principles, implicature, and politeness. Only three pet animals, namely bird, fish, and mouse have been selected to be studied and analyzed thoroughly. The samples of the study are collected from reliable English and Kurdish dictionaries and other resources. The findings show that some pet animal names have different frequencies in using, i.e., some are used more in English rather than in Kurdish, and vice versa. There are many contrasts rather than similarities in the meaning and utilizing of animal idioms in both languages. It was also found out that the pet animals violate all the maxims to get the idiomatic meaning; the most common type of implicature is the conversational one and most of the expressions are used negatively in terms of politeness.